Contribution of subgenomes to the transcriptome and their intertwined regulation in the allopolyploid Coffea arabica grown at contrasted temperatures. Issue 1 (24th June 2013) - Combes, Marie‐Christine; Dereeper, Alexis; Severac, Dany; Bertrand, Benoît; Lashermes, Philippe
Summary: Polyploidy has occurred throughout the evolutionary history of plants and led to diversification and plant ecological adaptation. Functional plasticity of duplicate genes is believed to play a major role in the environmental adaptation of polyploids. In this context, we characterized genome‐wide homoeologous gene expression in Coffea arabica, a recent allopolyploid combining two subgenomes that derive from two closely related diploid species, and investigated its variation in response to changing environment. The transcriptome of leaves of C. arabica cultivated at different growing temperatures suitable for one or the other parental species was examined using RNA‐sequencing. The relative contribution of homoeologs to gene expression was estimated for 9959 and 10 628 genes in warm and cold conditions, respectively. Whatever the growing conditions, 65% of the genes showed equivalent levels of homoeologous gene expression. In 92% of the genes, relative homoeologous gene expression varied < 10% between growing temperatures. The subgenome contributions to the transcriptome appeared to be only marginally altered by the different conditions (involving intertwined regulations of homeologs) suggesting that C . arabica 's ability to tolerate a broader range of growing temperatures than its diploid parents does not result from differential use of homoeologs.